2013
DOI: 10.1038/nature11932
|View full text |Cite
|
Sign up to set email alerts
|

Electrical image of passive mantle upwelling beneath the northern East Pacific Rise

Abstract: Melt generated by mantle upwelling is fundamental to the production of new oceanic crust at mid-ocean ridges, yet the forces controlling this process are debated. Passive-flow models predict symmetric upwelling due to viscous drag from the diverging tectonic plates, but have been challenged by geophysical observations of asymmetric upwelling that suggest anomalous mantle pressure and temperature gradients, and by observations of concentrated upwelling centres consistent with active models where buoyancy forces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(147 citation statements)
references
References 31 publications
11
136
0
Order By: Relevance
“…Low seismic wave speed ( 9 , 11 ) and high electrical conductivities ( 10 ) are strong evidence that melt plays an important role in controlling the physical properties of MOR mantle down to depths of >200 km. We find that a model with melt in a rectangular region down to a depth of 120 km requires 2% melt throughout to produce the required 1.7 s of normalΔtS*.…”
Section: Discussionmentioning
confidence: 99%
“…Low seismic wave speed ( 9 , 11 ) and high electrical conductivities ( 10 ) are strong evidence that melt plays an important role in controlling the physical properties of MOR mantle down to depths of >200 km. We find that a model with melt in a rectangular region down to a depth of 120 km requires 2% melt throughout to produce the required 1.7 s of normalΔtS*.…”
Section: Discussionmentioning
confidence: 99%
“…In the upper mantle, conductivity anomalies have been found associated with subduction zones and spreading centres and have been interpreted as partial melt and upwelling asthenosphere (e.g., Naif et al 2013;Key et al 2013;Rippe et al 2013). The long-period 3-D MT model obtained from array data in the north-western United States includes interpretations for upper mantle conductivity heterogeneities in a variety of different tectonic settings (Meqbel et al 2014).…”
Section: What Causes Conductivity Anomalies In the Mantlementioning
confidence: 98%
“…A broadband magnetotelluric survey was carried out across the northern East Pacific Rise by Key et al (2013). This study revealed a more detailed picture of the upper mantle and mantle upwelling beneath the ridge, providing constraints on melting processes and the volatile content of the mantle.…”
Section: Mantle Upwelling and Flow: The East Pacific Risementioning
confidence: 99%
“…Performances required for the geomagnetic field measurements are derived from the strength of Earth's main field as background, and fluctuation range and frequency of the local geomagnetic variation (e.g., Jacobs 1987). These are roughly defined as dynamic range of ± 60,000 nT, accuracy of ~ 0.1 nT, and sampling frequency of > 2 Hz.…”
Section: System Requirements For Observing Temporal Geomagnetic Fieldmentioning
confidence: 99%